Immobilization of chromium enhanced by arbuscular mycorrhizal fungi in semi-aquatic habitats with biochar addition - Chen, Zhongbing; Hu, Bo; Hu, Shanshan; Vogel-Mikuš, Katarina; Pongrac, Paula; Vymazal, Jan (Journal of hazardous materials, 2022)
Arbuscular mycorrhizal fungi (AMF) exhibit great potential in heavy-metal immobilization in semi-aquatic habitats. Under high heavy-metal stress, however, the role of AMF is limited, and the detoxification mechanism of AMF in heavy metals' stabilization remains unclear. This study investigated the effects of AMF on a wetland plant (Iris pseudacorus) and chromium (Cr) immobilization at different water depths in semi-aquatic habitats with biochar addition. Results showed that AMF increased the physiological and photosynthetic functions in I. pseudacorus under Cr exposures. Besides, AMF alleviated the accumulation of reactive oxygen species and lipid peroxidation by enhancing the antioxidant enzyme activities. AMF and biochar significantly decreased Cr concentrations in outlet water and increased Cr accumulation in I. pseudacorus. Besides, biochar also vastly improved Cr accumulation in the substrate under the fluctuating water depth. AMF reduced Cr bioavailability in the substrate, with Cr (Ⅵ) concentrations and acid-soluble forms of Cr decreased by 0.3-64.5% and 19.0-40.8%, respectively. Micro-proton-induced X-ray emission was used to determine element localization and revealed that AMF improved the nutrients uptake by wetland plants and inhibited Cr translocation from roots to shoots. Overall, this study demonstrated that the interaction between AMF and biochar could significantly enhance the immobilization of high Cr concentrations in semi-aquatic habitats.
Keywords: rostliny; Cr immobilization; voda; dřevěné a živočišné uhlí; Water; Arbuscular mycorrhizal fungi; Plants; mykorhiza; Ecosystem; Wetland plants behaviour; ekosystém; Charcoal; chrom; Mycorrhizae; Metals, Heavy; těžké kovy; houby; Plant Roots; Water depths; Fungi; Biochar; kořeny rostlin; Chromium